The economic burden of common adverse events associated with metastatic colorectal cancer treatment in the United States. (2nd January 2017) - Latremouille-Viau, Dominick; Chang, Jane; Guerin, Annie; Shi, Sherry; Wang, Ed; Yu, Justin; Ngai, Christopher
Abstract: Aims: Adverse events (AEs) associated with treatments for metastatic colorectal cancer (mCRC) may compromise the course of treatment, impact quality-of-life, and increase healthcare resource utilization. This study assessed the direct healthcare costs of common AEs among mCRC patients in the US. Methods: Adult mCRC patients treated with chemotherapy or targeted therapies were identified from administrative claims databases (2009–2014). Up to the first three mCRC treatment episodes per patient were considered and categorized as with or without the AE system/organ category during the episode. Total healthcare costs (2014 USD) were measured by treatment episode and reported on a monthly basis. Treatment episodes with the AE category were matched by treatment type and line of treatment to those without the AE category. Adjusted total cost differences were estimated by comparing costs during treatment episodes with vs without the AE category using multivariate regression models; p -values were estimated with bootstrap. Results: A total of 4158 patients with ≥1 mCRC treatment episode were included (mean age = 59 years; 58% male; 60% with liver and 14% with lung metastases; 2, 261 [54%] with a second and 1, 115 [27%] with a third episode). On average, two treatment episodes were observed per patient with an average length of 166 days per episode. Adjusted monthly total cost difference by AE category included hematologic (1, 480), respiratory (1, 253), endocrine/metabolic (1, 213), central nervous system (CNS; 1, 136), and cardiovascular (1, 036; all p < .05). Limitations: Claims do not include information on the cause of AEs, and potentially less severe AEs may not have been reported by the physician when billing the medical service. This study aimed to assess the association between costs and AEs and not the causation of AEs by treatment. Conclusions: The most costly AEs among mCRC patients were hematologic, followed by respiratory, endocrine/metabolic, CNS, and cardiovascular.